Separate roles for Med12 and Wnt signaling in regulation of oxytocin expression - Emma D. Spikol; Eric Glasgow (Biology Open, 2018)
Transcriptional control of oxytocinergic cell development influences social, sexual, and appetite related behaviors and is implicated in disorders such as autism and Prader-Willi syndrome. Mediator 12 (Med12) is a transcriptional coactivator required for multiple facets of brain development including subsets of serotonergic and dopaminergic neurons. We surveyed hormone gene expression within the hypothalamo-pituitary axis of med12 mutant zebrafish embryos with a focus on oxytocin (oxt) expression. Some transcripts, such as oxt, vasopressin (avp) and corticotrophin releasing hormone (crh) are undetectable in the med12 mutant, while others are upregulated or downregulated to varying degrees. In med12 mutants, the expression patterns of upstream transcriptional regulators of oxytocinergic cell development remain largely intact in the pre-optic area, suggesting a more direct influence of Med12 on oxt expression. We show that Med12 is required for Wnt signaling in zebrafish. However, oxt expression is unaffected in Wnt-inhibited embryos indicating independence of Wnt signaling. In fact, overactive Wnt signaling inhibits oxt expression, and we identify a Wnt-sensitive period starting at 24 h post fertilization (hpf). Thus, Med12 and repression of Wnt signaling display critical but unrelated roles in regulating oxt expression.